Assessing the impact of foundational ballet training on dance technique acquisition among primary school children in China - Bingqian, Lu (Theory and Practice of Physical Culture, 2026)
Objective of the study is to assess the effectiveness of basic ballet training for primary school children of the People’s Republic of China in the process of teaching them dance technique. Methods and structure of the study. The study was conducted during the 2024/2025 academic year in primary classes of general education schools in China. As a result of the experiment, experts (n=2), holding the highest coaching qualification in ballroom dancing, assessed the quality of movements during the performance of technical dance elements within the framework of basic training, using a 5-point grading system. Results and conclusions. In the control group, the quality of movement of the pupils before the experiment was rated at 6.67 points, with a standard deviation of 0.41. During the experiment, this indicator increased by 0.80 points and amounted to 6.75 points, with a standard deviation of 0.37 points. Despite the fact that the spread of indicators decreased slightly, it was nevertheless not possible to achieve a significant improvement (p>0.05). The results obtained indicate that the small increase could have been associated with the natural maturation of the children, habituation to repeated exercises, but not with the training programme itself. The conducted study proves that ballet dynamic technique effectively develops muscular abilities, range of motion, strength and agility as the main components of successful mastery of dance elements.